Are decorin gene variants associated with anterior cruciate ligament rupture susceptibility? - Łosińska, Kinga; Rzeszutko-Bełzowska, Agata; Ficek, Krzysztof; September, Alison V. (Biology of Sport, 2025)
This study aimed to investigate whether two DCN gene single nucleotide polymorphisms (SNPs), rs13312816 (T > A) and rs516115 (A > G), are associated with the risk and severity of anterior cruciate ligament (ACL) injury. A total of 296 physically active, unrelated Caucasian males participated: 160 with noncontact ACL injuries and 136 healthy controls. Genotyping was conducted using TaqMan assays. Logistic regression and haplotype-based analyses were performed, adjusting for age and body mass. The minor A allele of rs13312816 was significantly more frequent in ACL cases than in controls (8.54% vs. 2.94%, P = 0.0047; OR = 3.08, 95% CI: 1.33–7.98). Individuals with the A/T genotype had higher odds of injury compared to T/T carriers (P adj = 0.008; OR = 3.3, 95% CI: 1.44–7.53). No associations were found for rs516115 in the case–control comparison. Haplotype analysis showed that individuals with the [A;G] haplotype had increased odds of ACL injury (P adj = 0.0095; OR = 3.29, 95% CI: 1.44–7.52). Within the injured group, rs13312816 A/T genotype was associated with multiple injuries (ACLF) (P adj = 0.010; OR = 3.19, 95% CI: 1.36–7.48). For rs516115, both A/G (P adjj < 0.0001; OR = 6.03, 95% CI: 2.83–12.83) and G/G genotypes (P adj < 0.0001; OR = 9.71, 95% CI: 2.57–36.77) were linked to ACLF. Haplotype analysis confirmed increased odds for multiple injuries in carriers of [A;G] (P adj = 0.0099; OR = 3.34, 95% CI: 1.33–8.35) and [T;G] haplotypes (Pa dj < 0.0001; OR = 4.79, 95% CI: 2.35–9.79). These findings suggest that DCN genetic variants, especially rs13312816 and specific haplotypes, contribute to ACL injury susceptibility and recurrence.